effects of water availability on root growth and morphology in an Amazon rainforest - Metcalfe, Daniel B; Meir, Patrick; Aragão, Luiz Eduardo O. C; da Costa, Antonio C. L; Braga, Alan P; Gonçalves, Paulo H. L; de Athaydes Silva Junior, Joao; de Almeida, Samuel S; Dawson, Lorna A; Malhi, Yadvinder; Williams, Mathew (Plant and soil, 2008)
This study examined how root growth and morphology were affected by variation in soil moisture at four Amazon rainforest sites with contrasting vegetation and soil types. Mean annual site root mass, length and surface area growth ranged between 3-7 t ha⁻¹, 2-4 km m⁻² and 8-12 m² m⁻² respectively. Mean site specific root length and surface area varied between 8-10 km kg⁻¹ and 24-34 m² kg⁻¹. Growth of root mass, length and surface area was lower when soil water was depleted (P < 0.001) while specific root length and surface area showed the opposite pattern (P < 0.001). These results indicate that changes in root length and surface area per unit mass, and pulses in root growth to exploit transient periods of high soil water availability may be important means for trees in this ecosystem to increase nutrient and water uptake under seasonal and longer-term drought conditions.